Quantitative risk assessment of acquiring campylobacteriosis from consumption of ready-to-eat beef in Arusha Municipality, Tanzania - Toyomaki, H.; Mahundi, E.; Ishihara, K.; Kurwijila, Lusato R.; Grace, Delia; Makita, K. (Japan Society of Veterinary Epidemiology, 2011)
Worldwide, thermophilic Campylobacter, especially C. jejuni and C. coli is one of the most important causes of food borne illness. In the present study, a risk for campylobacteriosis due to consumption of ready-to-eat beef in Arusha, Tanzania was assessed. Between January and March 2010, 18 beer bars serving ready to eat beef were surveyed: 45 roast beef (nyama choma in Swahili language) and 42 skewer beef (mishikaki) were collected and served for isolation of C. jejuni and C. coli. The number of customers and average sales per day were also assessed. The second survey was conducted in September 2010 to obtain the most probable number (MPN) of C. jejuni and C. coli. Forty beer bars were surveyed: 30 roast beef and 10 roast chicken samples were collected and examined. A risk model was developed based on public and survey data. Dose-response relationship was modeled using medical records obtained from a separate study and literatures. Monte Carlo simulation was run for 5,000 iterations and sensitivity analysis was run for 500 iterations. Bayesian inference from two surveys showed that the contamination rates of nyama choma and mishikaki were 7.7% (90%CI: 4.3%-11.8%) and 34.7% (90%CI: 21.3%-49.1%) respectively. The MPN was 0.37/g (90%CI: 0.03-1.2). Every day, 1.4% (90% CI: 0.8-2.3%) of customers consuming either nyama choma or mishikaki in pubs in Arusha was estimated to develop campylobacteriosis. The annual incidence was 248 (95%CI: 127-406) per 1000 people among whole population of Arusha Municipality and one fourth of people was estimated to become sick once a year. The most sensitive factors were contamination rate of ready-to-eat beef and the cfu per gram. From observation, beef was well roasted and the high prevalence could be due to post-roast contamination. Hygiene training focused on such contamination would reduce the incidence greatly.